Gender Features of Verbal Representation of the Concept "Gender Inequality" by University Students - Tetiana Kostina; Diana Drozdova; Iryna Bulakh (East European Journal of Psycholinguistics, 2022)
The article presents a study of the verbal representation of the concept of "gender inequality" in student youth. The research aims to determine and experimentally investigate the content of the "gender inequality" concept in the students' linguistic consciousness and to analyze its verbally expressed gender features. Verbal representations were obtained based on the use of a controlled association test. The study involved 309 undergraduate and graduate students (199 women and 110 men) of various specialities, aged 17 to 25. According to the experiment results, 840 word-tokens were obtained, including 23 phrases; 160 associations presented single reactions. Gender analysis showed that women provided 539 responses, including 530 verbal (176 original) reactions and nine rejections; men provided 319 reactions: 310 verbal reactions (103 original) and nine rejections. Gender characteristics were determined based on calculating associates' brightness index and forming the core of the associative field. Among the most frequent were woman (.28), men (.24), and feminism (.12). Cognitive interpretation of the data showed that for women, the concept of "gender inequality" has a more negative emotional connotation than for men. For a significant number of women, gender inequality includes experiences that are associated with sexism (.08), discrimination (.07), and violence (.07). Analysis of male associations has shown that the concept of "gender inequality" in men has a less emotional response and is presented at a more abstract (theoretical) level.